2006
DOI: 10.1016/j.ejcts.2006.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Expression of hypoxia-inducible factor-1 alpha and its prognostic significance in small-sized adenocarcinomas of the lung

Abstract: Immunohistochemical staining of HIF-1 alpha, along with examination of metastatic potential via vascular pathways, may be valid defining a subpopulation of patients with small-sized adenocarcinoma of the lung whose tumors have aggressive angiogenesis potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 22 publications
1
33
0
Order By: Relevance
“…57,58 However, a large proportion of human tumors exhibit VEGF-A expression in the absence of HIF-1␣. 39 Although the VEGF-A promoter contains a HIF-1␣ binding site, 58 our study demonstrated negligible HIF-1␣ expression in lung cancer cells cultivated under ordinary conditions, and luciferase reporter assays revealed no significant association between the HIF-1␣ binding site and VEGF-A promoter activity.…”
Section: Discussionmentioning
confidence: 99%
“…57,58 However, a large proportion of human tumors exhibit VEGF-A expression in the absence of HIF-1␣. 39 Although the VEGF-A promoter contains a HIF-1␣ binding site, 58 our study demonstrated negligible HIF-1␣ expression in lung cancer cells cultivated under ordinary conditions, and luciferase reporter assays revealed no significant association between the HIF-1␣ binding site and VEGF-A promoter activity.…”
Section: Discussionmentioning
confidence: 99%
“…Low VEGF levels were reported in adenocarcinoma in situ, that is, formerly bronchioloalveolar carcinoma, compared with "conventional adenocarcinoma" (Saad et al 2004). Enatsu et al (2006) observed an association between hypoxia-inducible factor-1α (HIF-1α) and VEGF-A expression in pulmonary adenocarcinomas, and little or no reactivity of HIF-1α was observed in the bronchioloalveolar components, in contrast to the solid components of adenocarcinomas with mixed subtypes. Therefore, the absence of lymphangiogenesis in the areas of lepidic growth might reflect the absence of VEGF secretion by tumor cells, in contrast to the VEGF-C secretion in invasive adenocarcinomas reported by Saintigny et al (2007).…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of angiogenic pathways by HIF-1alpha has been seen in NSCLC and it is reported as a common event associated with poor prognosis [28,[39][40][41] .…”
Section: Hif-1alpha and Angiogenesismentioning
confidence: 99%
“…HIF-1alpha was reported to be localized both in the nucleus and the cytoplasm of tumor cells. Some authors consider only nuclear staining as positive [31,34] while others take into account cytoplasmic reactivity as well [28,30,39] . The presence and the biological significance of cytoplasmic HIF-1alpha staining in tissue samples are controversial.…”
Section: Hif-1alpha Evaluation In Tissue Specimensmentioning
confidence: 99%
See 1 more Smart Citation